2016
DOI: 10.1016/j.bbrep.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the LP28 strain-specific exopolysaccharide biosynthetic gene cluster found in the whole circular genome of Pediococcus pentosaceus

Abstract: We have previously isolated a lactic acid bacterium (LAB), Pediococcus pentosaceus LP28, from the longan fruit Euphoria longana. Since the plant-derived LAB strain produces an extracellular polysaccharide (EPS), in this study, we analyzed the chemical structure and the biosynthesizing genes for the EPS.The EPS, which was purified from the LP28 culture broth, was classified into acidic and neutral EPSs with a molecular mass of about 50 kDa and 40 kDa, respectively. The acidic EPS consisted of glucose, galactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
9
0
2
Order By: Relevance
“…pentosaceus isolates assayed produced EPS containing from 2.4% (isolate FF78) to 6.7% (isolate FF71) mannose. Again, these results agreed with those of a research study [ 70 ] carried out on the EPS extracted from fruit-sourced isolates ascribed to P . pentosaceus , which were mainly composed of glucose, galactose, and mannose.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…pentosaceus isolates assayed produced EPS containing from 2.4% (isolate FF78) to 6.7% (isolate FF71) mannose. Again, these results agreed with those of a research study [ 70 ] carried out on the EPS extracted from fruit-sourced isolates ascribed to P . pentosaceus , which were mainly composed of glucose, galactose, and mannose.…”
Section: Resultssupporting
confidence: 91%
“…This could be explained by a possible variation in one or both the primer binding sites of the EPS genes, which in turn might have hindered the successful amplification of these target genes. An alternative explanation relies on the involvement of other genes in EPS synthesis, as suggested by a recent investigation [70] on the EPS-biosynthetic gene cluster of a P. pentosaceus strain (LP28) isolated from Euphoria longana, where 12 open reading frames (ORFs) containing a priming enzyme, five glycosyltransferases, and a putative polysaccharide pyruvyl transferase were identified.…”
Section: Molecular Detection Of Eps-related Genesmentioning
confidence: 99%
“…7,8) In fact, the LY45 strain isolated from lychee can also grow at that concentration of NaCl. The LY45 and PY45 strains grew even at 50°C, whereas P. pentosaceus LP28, which produces an EPS modified by pyruvate residue, 14) did not (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…9,10) EPSs have been shown to benefit human health by their immunomodulation, anti-gastritis, anti-ulcer, and anti-virus activities. [11][12][13] We have shown that P. pentosaceus LP28 has the strain-specific EPS biosynthetic gene cluster, 14) and intake of the strain is effective to improve the high fat diet-induced obesity and fatty liver of the mice. 6) Furthermore, the strain is also useful to reduce body fat and body weight in human clinical study.…”
mentioning
confidence: 99%
“…paracasei IJH-SONE68. A modified semi-defined medium (SDM) supplemented with a vitamin mixture (0.2 v / v %) and trace element solution (0.1 v / v %) instead of yeast nitrogen bases was used as a main culture medium [55,56,57].…”
Section: Methodsmentioning
confidence: 99%